Interventions to promote family member involvement in adult critical care settings: a systematic review - Sally Brearley; Simon Fletcher; Anne Marie Rafferty; Julia Philippou; Andreas Xyrichis; Marius Terblanche (BMJ Open)
Objective To identify, appraise and synthesise evidence of interventions designed to promote family member involvement in adult critical care units; and to develop a working typology of interventions for use by health professionals and family members.Design Mixed-method systematic review.Data sources Bibliographic databases were searched without date restriction up to June 2019: MEDLINE, EMBASE and CINAHL; the Cochrane Central Register of Controlled Trials, Joanna Briggs and Cochrane Libraries. Back issues of leading critical care and patient experience journals were manually searched, as were the reference lists of included studies. All evaluation studies of relevant intervention activities were included; all research designs and outcome measures were eligible. Due to heterogeneity in interventions, designs and outcome measures, the synthesis followed a narrative approach. Service users met with the research team termly.Results Out of 4962 possible citations, a total of 20 studies were included. The overall evidence base was assessed as moderate to weak. Six categories of interventions were identified: environmental unit changes (n=2), web-based support (n=4), discussion-based support (n=6), multicomponent support (n=4), participation in rounds (n=3) and participation in physical care (n=1). Clinical and methodological heterogeneity across studies hindered meta-analysis, hence a narrative synthesis was pursued. Six main outcomes were identified, grouped under two categories: (i) involvement outcomes: communication (mean difference ranged from 6.39 to 8.83), decision-making (mean difference ranged from −0.8 to 5.85), satisfaction (mean difference ranged from 0.15 to 2.48); and (ii) health outcomes: family trauma (mean difference ranged from −7.12 to 0.9), family well-being (mean difference ranged from −0.7 to −4), patient outcomes (relative risk ranged from 1.27 to 4.91). The findings from the qualitative studies were thematically analysed to identify features of the interventions that participants perceived to influence effectiveness. Synthesised into five overarching categories (practicality, development, interaction, reflexivity and bridging), these can serve as principles to inform the future design and development of more refined family member involvement interventions.Conclusions Future interventions should be developed with much closer family member input and designed by considering the key features we identified. We call for future interventions to be multilayered and allow for a greater or lesser level, and different kinds, of involvement for family members. Choice of intervention should be informed by a baseline diagnostic of family members’ needs, readiness and preparedness for involvement.PROSPERO registration CRD42018086325.